Report of a Study Team Industrial Potential Survey Madhya Pradesh - Planning Commission (Planning Commission, 1971)
Regional balance or reduction in the disparities with regard to the level and the rate of development amongst the different regions has been all along one of the principal objectives of planned development in India. However, since this objective was attained only to a very limited extent during the first three Five Year Plans, a new and a different approach has been initiated since 1968 for the attainment of this objective. The primary responsibility for this purpose would be that of the Government—both Central and State; however, the financial institutions are expected to play a catalytic role in promoting regionally balanced development.
Industrial Potential Survey, Madhya Pradesh